(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2021)
The purpose of this paper was to analyze the forms of protection and fulfillment of human rights by local governments against the followers of the Tolotang faith in accessing their right to health service as minority group in Sidenreng Rappang District, South Sulawesi Province. The type of research used was normative legal research using a statutory approach. The results showed that The followers of the Tolotang faith have been recognized by the state, and weregiven space to worship based on their beliefs. Also Tolotang faith have recognize by the local goverment as part of the community in Sidenreng Rappang who have the same access in order to get health service from any medical stuff, doctor, clinic , hospital whenever they need it.The findings of this article can provide insights into the forms of protection and fulfillment of human rights by local governments against the followers of the Tolotang faith inin in accessing their right to health service as minority group in Sidenreng Rappang District, South Sulawesi Province.The followers of the Tolotang faith have been recognized by the state, and weregiven space to worship based on their beliefs. Also Tolotang faith have recognize by the local goverment as part of the community in Sidenreng Rappang who have the same access in order to get health service from any medical stuff, doctor, clinic , hospital whenever they need it.